Effects of Treatment Type on Alcohol Consumption Partially Mediated by Alcoholics Anonymous Attendance. (21st March 2018) - Karriker-Jaffe, Katherine J.; Klinger, Jamie L.; Witbrodt, Jane; Kaskutas, Lee Ann
ABSTRACT: Background : As insurance coverage, funding sources and venues for drug and alcohol treatment evolve in the United States, it is important to assess how the type of treatment received may impact long-term outcomes. The current study aims were to examine effects of treatment type on alcohol consumption in the year after treatment intake and to test mediators of effects of treatment type on later alcohol use. Methods : Longitudinal data from clients in inpatient and outpatient alcohol treatment programs in California (n = 560) were used in ordinary least squares path analysis adjusting for respondent characteristics typically associated with both treatment completion and alcohol use. The primary outcome was amount of alcohol consumed in the 12 months after treatment entry; hypothesized mediators were treatment duration and participation in Alcoholics Anonymous (AA). Results : Despite higher baseline problem severity and a shorter treatment duration, inpatient clients consumed less alcohol after treatment than outpatient clients (B [95% CI] = −0.95 [−1.67, −0.23]). AA involvement was a significant mediator of the relationship between treatment type and alcohol consumption, with inpatient clients being more involved in AA and also drinking less after treatment than outpatient clients; the bias-corrected bootstrap 95% confidence interval for the indirect effect (B = −0.20) was entirely below zero (−0.43 to −0.05). Conclusions : Outpatient clients may benefit from customized posttreatment recommendations to identify additional resources to assist in the recovery process during the first year after treatment.